The Feasibility of Encapsulated Embryonic Medullary Reticular Cells to Grow and Differentiate Into Neurons in Functionalized Gelatin-Based Hydrogels - Magariños, Ana M.; Pedron, Sara; Creixell, Marc; Kilinc, Murat; Tabansky, Inna; Pfaff, Donald W.; Harley, Brendan A. C. (Frontiers in Materials, 2018)
The study of the behavior of embryonic neurons in controlled in vitro conditions require methodologies that take advantage of advanced tissue engineering approaches to replicate elements of the developing brain extracellular matrix. We report here a series of experiments that explore the potential of photo-polymerized gelatin hydrogels to culture primary embryonic neurons. We employed large medullary reticular neurons whose activity is essential for brain arousal as well as a library of gelatin hydrogels that span a range of mechanical properties, inclusion of brain-mimetic hyaluronic acid, and adhesion peptides. These hydrogel platforms showed inherent capabilities to sustain neuronal viability and were permissive for neuronal differentiation, resulting in the development of neurite outgrowth under specific conditions. The maturation of embryonic medullary reticular cells took place in the absence of growth factors or other exogenous bioactive molecules. Immunocytochemistry labeling of neuron-specific tubulin confirmed the initiation of neural differentiation. Thus, this methodology provides an important validation for future studies of nerve cell growth and maintenance.